Recent advances in circuits and systems - Mastorakis, Nikos E. ([S.l.] : World Scientific Publishing Company, 1998)
A presentation of concepts, methods, algorithms, techniques, procedures and applications of the field of circuits and systems. Written by international specialists, it gives special emphasis to the interaction between the classic areas of systems theory (feedback control, circuits design and electronics) and the modern techniques of computational intelligence (neural networks, genetic algorithms, fuzzy logic and expert systems). The book is composed of four parts. The first is devoted to circuits and electronics and also includes power systems. Part Two refers to systems theory and control (H-infinity problems, feedback control, non-linear systems, robust stability and robust control, multivariable systems, hybrid systems and hydraulic systems). Part Three presents developments in robotics (theory and applications), while Part Four is devoted to computational intelligence in systems theory.